Design and fabrication of the portable artwork preservative device (PAPD) - Quanjin, Ma; Zhang, Zhenggang; M. R. M., Rejab; M. S., Idris; Bo, Zhang; M. H., Abdullah (Penerbit UMP, 2019)
Traditional artworks not only have the long history, but also offer the high economic value in the auction market. The artwork is commonly used paper or silk paper as raw material, which needs the relative harsh condition to save. However, there are generally three types of conditions to do harm to the valuable artworks, which are water, fire and earthquake or stealing conditions. In order to protect the artworks from irreversible damaged conditions, the portable artwork preservative device is designed to protect the artworks using rolling up the artwork method and keep it inside the artwork box. Three types of sensor modules have been selected in this study, which are used to detect the external conditions. It is concluded that this device shows the valid response performance, and it is automatedly rolled up the artwork around 10 s when it detects the signals from three sensor modules. In addition, the joystick module is used to control the artwork movement manually.